PELAKSANAAN TERTIB ADMINISTRASI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA KANTOR LURAH NAMBO KECAMATAN NAMBO KOTA KENDARI - Suriyani BB; La Ode Muhammad Elwan; Iwan P; Usman (Journal Publicuho, 2025)
This study aims to analyse the implementation of administrative order in improving public service quality at the Nambo Village Office, Nambo District, Kendari City. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The study's results show that, although the Nambo Village Office has made efforts to implement administrative orders through a structured system, staff training, and the use of technology in data management, several challenges still affect public service quality. These challenges include complex procedures, long processing times, limited human resources, and a lack of transparency in budget management. On the other hand, the quality of public service at the Nambo Village Office is generally good, with adequate facilities, reliable service, and a commitment from the office to provide fast, efficient, and transparent services. However, there are issues with inconsistent staff responsiveness, limited facilities, and technical challenges that affect the public's comfort. Therefore, this study recommends improvements in efficiency, transparency, and the enhancement of professionalism and responsiveness of staff to improve the quality of public service at the Nambo Village Office.